Flexible GaAs photodetector arrays hetero-epitaxially grown on GaP/Si for a low-cost III-V wearable photonics platform - Hong, Namgi; Chu, Rafael Jumar; Kang, Soo Seok; Ryu, Geunhwan; Han, Jae-Hoon; Yu, Ki Jun; Jung, Daehwan; Choi, Won Jun (OPTICAL SOC AMER, 2020)
We demonstrate flexible GaAs photodetector arrays that were hetero-epitaxially grown on a Si wafer for a new cost-effective and reliable wearable optoelectronics platform. A high crystalline quality GaAs layer was transferred onto a flexible foreign substrate and excellent retention of device performance was demonstrated by measuring the optical responsivities and dark currents. Optical simulation proves that the metal stacks used for wafer bonding serve as a back-reflector and enhance GaAs photodetector responsivity via a resonant-cavity effect. Device durability was also tested by bending 1000 times and no performance degradation was observed. This work paves a way for a cost-effective and flexible III-V optoelectronics technology with high durability. (C) 2020 Optical Society of America under the terms of the OSA Open Access Publishing Agreement